Development and applications of aluminum alloys for aerospace industry - Li, Shuang–Shuang; Yue, Xin; Li, Qing–Yuan; Peng, He–Li; Dong, Bai–Xin; Liu, Tian–Shu; Yang, Hong–Yu; Fan, Jun; Shu, Shi–Li; Qiu, Feng; Jiang, Qi–Chuan (Journal of materials research and technology, 2023)
There is an increasingly urgent need of lightweight components in aerospace industry, among which aluminum (Al) alloys have been the optimal materials of choice for aircraft structural parts since being used in the Junkers F.13 aircraft in the 1920s. Compared to other metal materials, Al alloys have a lower density, and the use of Al alloys reduces the total weight of the aircraft and improves fuel efficiency and load capacity. Meanwhile, the strength and hardness of Al alloys with alloying and heat treatment can be significantly enhanced for uses in high loads and vibration environments. Furthermore, in the harsh aerospace environment, aircraft may receive various climatic conditions and chemical corrosion. Due to good corrosion and fatigue resistance, Al alloys demonstrate excellent performance under these conditions, ensuring the long–term service life of aircraft. In addition, Al alloys have good recyclability, and they can be recycled to reduce resource consumption and environmental load, in line with the principle of sustainable development. In recent years, although composites have been widely used in aerospace, high–strength Al alloys are still in an indispensable position. Therefore, this article reviews the progress and applications of Al alloys commonly used in aerospace. The common strengthening methods and advanced manufacturing and processing technologies of Al alloy are also discussed, which can provide references for the development of advanced high–performance aviation Al alloys in the future.